Kinetic study of in-pipe water flow for power generation / Venuthan Surendaran - Venuthan , Surendaran (2020)
In-pipe turbine generator has a potential to harvest energy from an existing water flow from distribution pipe which have natural and pumping capacity. That flow will be used to convert kinetic energy from the pipe to rotate the turbine. In turn, the turbine may be connected to a generator to produce electric power. The fact that the in-pipe turbine generator will be a useful energy harvesting tool with potential with industrial application is recommended by many scholars. However, there is a concern where there are many types and sizes of pipe that is readily used in the water works industry. Since that concern arises a kinetic study is required to analyze and observe the flow, velocity, and kinetic energy present in different pipes. A kinetic study of pipe water flow will further enhance and familiarize industry players with the in-pipe turbine generator. The reason is that a kinetic study will give more information to turbine manufacturer to size turbine accordingly based on flow data which is available. Observing the simulation results obtained from various pipe dimensions there is a trend that kinetic energy is observed maximum at a reduced diametrical point of the pipe rather than at the pipe’s maximum diameter. When sizing turbine proper attention must be given details such as maximum velocity at various diameter to be able to maximize rate of energy harvesting. A turbine cannot be sized to be the same size as the pipe diameter as it will not be able to harvest energy at an optimum rate. This study focusses on geometry of different pipe sizes to evaluate the flow, velocity, and kinetic energy. The results obtained from this study is hoped to aid in proper sizing of turbine for industrial level application